Are Variable Annuities the Answer to Inflation? - McCracken, Paul W. (Journal of Finance, 1956)
THE MAJOR REASON for interest in variable annuities stems from the possibility that they would provide one answer to the problem of hedging against price inflation.Two questions are, of course, involved.Would these, in fact, provide a reasonably adequate hedge against inflation?Is the prospect for chronic price infiation serious enough to warrant this substantial departure from financial orthodoxy? IThe issues involved in this first question have been at the focus of many discussions in the financial community.Two or three conclusions seem obvious.Funds invested in fluctuating-price assets will provide substantially more of a hedge against inflation than those invested in more orthodox ways.The hedge is not perfect, and individual situations could certainly arise where the results would work out badly.Stock prices and the cost of living do move conversely at times.The timing of benefit payments may be adverse.The selection of individual securities may be sufficiently unfortunate so that a portfolio might behave worse than stock averages.These are, however, questions which must be explored by those closer to the specific problems which the financial industry might face if it were to move actively in this direction.My comments here will be largely confined to the second question, i.e., what are the longer-run price-level prospects?This, of course, is a fundamental question, and how it is answered importantly determines whether these other matters are academic or real-life considerations. I1In the considerable amount of postwar discussion of price-level prospects, six reasons have emerged for expecting that we are in an "age of inflation," with the long-run trend of the dollar's purchasing power declining?University of Michigan 1.The phrase is from a series of articles on "Agenda for the Age of Inflation" beginning in the Economist (August 18, 1951).Much of the material in this section appeared